2021
DOI: 10.1039/d0ob02162h
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry and biology of fungal meroterpenoids (2009–2019)

Abstract: The structural features, biological activities, and fungal biodiversity of 1585 new meroterpenoids were comprehensively overviewed (2009–2019).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 466 publications
0
85
0
Order By: Relevance
“…(iii) Gozari et al [31] reviewed only 190 meroterpenoids from bacteria and fungi that showed significant preclinical effects. (iv) Jiang et al [32] summarized the described 1585 fungal meroterpenoids in 2009-2019.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Gozari et al [31] reviewed only 190 meroterpenoids from bacteria and fungi that showed significant preclinical effects. (iv) Jiang et al [32] summarized the described 1585 fungal meroterpenoids in 2009-2019.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides and triterpenoids are representative of the important biologically active components of Ganoderma ( Wang et al, 2020 ). Recent ongoing research studies exploring Ganoderma demonstrated that it contains meroterpenoid components that possess extensive biological activities, such as renal protection and neuroprotection, anti-inflammation, -tumor and -oxidation properties, and analgesic effects ( Jiang et al, 2021 ). These studies led to a deeper understanding of the components of Ganoderma and insight into active ingredients responsible for its traditional medical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal meroterpenoids are secondary metabolites from mixed terpene-biosynthetic origins. 386 Based on their nonterpenoid starting scaffolds, meroterpenoids were classified into four categories: polyketide–terpenoid, indole-terpenoid, shikimate-terpenoid, and miscellaneou meroterpenoids.…”
Section: Secondary Metabolites From Mangrove Fungimentioning
confidence: 99%